1998
DOI: 10.1021/js970090e
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Pluronic F127-Based Controlled-Release Ocular Delivery Systems for Pilocarpine

Abstract: The overall objective of this study was to develop pluronic F127 (PF127)-containing formulations of pilocarpine hydrochloride (PHCL) suitable for controlled-release ocular delivery of PHCL. Various aqueous formulations were evaluated containing 1% w/v PHCL and 25% w/v PF127 alone or with one of the following additives present: poly(ethylene glycol) 4600 (PEG), poly(vinylpyrrolidone) 10,000 (PVP), poly(vinyl alcohol) 10,000 (PVA), methylcellulose 15 cP (MC), and hydroxypropyl methylcellulose 80-120 cP (HPMC). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(76 citation statements)
references
References 20 publications
5
71
0
Order By: Relevance
“…Pluronic F127 is known to provide sustained release and increased stability of drug molecules including peptides 9,11,26 and nonpeptides. 27 Our studies (unpublished data, 2005) on differential scanning analysis of PF127 gels containing Spantide II show no interaction of this peptide with the gel matrix. Therefore, this polymer offers better compatibility and release characteristics of Spantide II.…”
Section: E569mentioning
confidence: 71%
“…Pluronic F127 is known to provide sustained release and increased stability of drug molecules including peptides 9,11,26 and nonpeptides. 27 Our studies (unpublished data, 2005) on differential scanning analysis of PF127 gels containing Spantide II show no interaction of this peptide with the gel matrix. Therefore, this polymer offers better compatibility and release characteristics of Spantide II.…”
Section: E569mentioning
confidence: 71%
“…9 The combination of Poloxamer-407 and HPMC provides a drug delivery matrix with slower drug release compared to either component alone. 10,21,25,26 In the present studies, we examined the mobilization properties of Flt3L when formulated in a sustained release matrix composed of Poloxamer-407 and HPMC. Our pharmacokinetic analyses demonstrated that the administration of Flt3L formulated with PG (PG-Flt3L) resulted in sustained delivery.…”
mentioning
confidence: 99%
“…The viscosity values of PLO are higher than the rest of the excipients, which substantiates a lesser transfer from this base (Desai and Blanchard 1998). As far as the greater release from the Pluronic gel to that of PLO is concerned, it could be due to the greater filtration of water to the gel, which causes the fragmentation of the latter and complete release of the methimazole (Sambhaji et al 2004).…”
Section: In Vitro Releasementioning
confidence: 96%